Discovery of 3(S)-thiomethyl pyrrolidine ERK inhibitors for oncology. Issue 11 (15th June 2018) - Boga, Sobhana Babu; Alhassan, Abdul-Basit; Cooper, Alan B.; Doll, Ronald; Shih, Neng-Yang; Shipps, Gerald; Deng, Yongqi; Zhu, Hugh; Nan, Yang; Sun, Robert; Zhu, Liang; Desai, Jagdish; et al.
Graphical abstract: Highlights: Discovery of potent, selective and orally bioavailable ERK inhibitor for oncology. Synthesis of tert 3-( S )thiomethyl pyrrolidine based ERK inhibitors. Improved PK due to sulfur substitution-mitigation of amide bond cleavage. Abstract: Compound5 (SCH772984) was identified as a potent inhibitor of ERK1/2 with excellent selectivity against a panel of kinases (0/231 kinases tested @ 100 nM) and good cell proliferation activity, but suffered from poor PK (rat AUC PK @10 mpk = 0 μM h; F% = 0) which precluded further development. In an effort to identify novel ERK inhibitors with improved PK properties with respect to5, a systematic exploration of sterics and composition at the 3-position of the pyrrolidine led to the discovery of a novel 3( S )-thiomethyl pyrrolidine analog28 with vastly improved PK (rat AUC PK @10 mpk = 26 μM h; F% = 70).